2D projection-based software application for mobile C-arms optimises wire placement in the proximal femur – An experimental study. Issue 10 (October 2017) - Swartman, B.; Frere, D.; Wei, W.; Schnetzke, M.; Beisemann, N.; Keil, H.; Franke, J.; Grützner, P.A.; Vetter, S.Y.
Abstract: Purpose: A new software application can be used without fixed reference markers or a registration process in wire placement. The aim was to compare placement of Kirschner wires (K-wires) into the proximal femur with the software application versus the conventional method without guiding. As study hypothesis, we assumed less placement attempts, shorter procedure time and shorter fluoroscopy time using the software. The same precision inside a proximal femur bone model using the software application was premised. Methods: The software detects a K-wire within the 2D fluoroscopic image. By evaluating its direction and tip location, it superimposes a trajectory on the image, visualizing the intended direction of the K-wire. The K-wire was positioned in 20 artificial bones with the use of software by one surgeon; 20 bones served as conventional controls. A brass thumb tack was placed into the femoral head and its tip targeted with the wire. Number of placement attempts, duration of the procedure, duration of fluoroscopy time and distance to the target in a postoperative 3D scan were recorded. Results: Compared with the conventional method, use of the application showed fewer attempts for optimal wire placement (p = 0.026), shorter duration of surgery (p = 0.004), shorter fluoroscopy time (p = 0.024) and higher precision (p = 0.018). Final wire position was achieved in the first attempt in 17 out of 20 cases with the software and in 9 out of 20 cases with the conventional method. Conclusions: The study hypothesis was confirmed. The new application optimised the process of K-wire placement in the proximal femur in an artificial bone model while also improving precision. Benefits lie especially in the reduction of placement attempts and reduction of fluoroscopy time under the aspect of radiation protection. The software runs on a conventional image intensifier and can therefore be easily integrated into the daily surgical routine.